School bullying among migrant children in China: A cross-sectional study - Yang, Zhengmin; Tu, Ying; Qin, Zaihua; Liu, Xiaoqun; Lu, Dali (Frontiers in Psychology, 2022)
Background: Bullying is a serious public health concern affecting the physical and mental health of children. Migrant children are at higher risk of developing health problems. We conducted this study to investigate the prevalence of school bullying and its possible influencing factors of migrant children. Methods: A cross-sectional study was carried out in Hunan Province, China from April to July 2018. Multi-stage cluster sampling was adopted to achieve a representative sample covering both urban and rural areas. Migrant children are defined as those who migrate with one or both parents to other places and who do not have a hukou in their city of residence. The Chinese version of Olweus Bully/Victim Questionnaire was applied to measure children’s involvement in school bullying. Results: A total of 7607 students were surveyed, including 995 migrant children and 6612 non-migrant children. The prevalence of school bullying was significantly higher in migrant children than in non-migrant children ( χ2=22.740; p < 0.001). Binary regression analysis showed that male, middle school identity, more times of playing violent games, more social friends owning and being beaten by parents or caregivers may increase the risk of involvement of school bullying in migrant children. Conclusions: Migrant children showed a higher prevalence of school bullying than non-migrant children. Gender, grade, frequency of playing violent games, number of social friends and being beaten by parents or caregivers were associated with school bullying in migrant children.